2022
DOI: 10.3390/cancers14081935
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Predicts Major Complications after Resection for Primary Hepatocellular Carcinoma in Compensated Cirrhosis

Abstract: The burden of post-operative complications of patients undergoing liver resection for hepatocellular carcinoma (HCC) is a cause of morbidity and mortality. Recently, sarcopenia has been reported to influence the outcome of patients with cirrhosis. We aimed to assess factors associated with sarcopenia and its prognostic role in liver surgery candidates. We included all patients with compensated advanced chronic liver disease (cACLD) undergoing liver resection for primary HCC consecutively referred to the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Patients with low SMI are more likely to develop PHLF than those with high SMI. The reason for this may be that SMI reflects the nutritional status of the patient and is an indirect marker of the patient’s frailty, defined as a condition that can reflect a reduction in the patient’s physiological reserves and therefore may affect the outcome after surgery ( 21 , 22 ). ASA scores are now commonly used to assess a patient’s holistic composite fitness before anesthesia, and we found that patients with high ASA grades had a higher risk, which is consistent with previous studies ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low SMI are more likely to develop PHLF than those with high SMI. The reason for this may be that SMI reflects the nutritional status of the patient and is an indirect marker of the patient’s frailty, defined as a condition that can reflect a reduction in the patient’s physiological reserves and therefore may affect the outcome after surgery ( 21 , 22 ). ASA scores are now commonly used to assess a patient’s holistic composite fitness before anesthesia, and we found that patients with high ASA grades had a higher risk, which is consistent with previous studies ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the complication rate was not statistically significant in this study, we could find a trend towards higher rates of complications, including minor and major complications, in patients with sarcopenia. In addition, Giovanni Marasco et al reported similar results that sarcopenia was associated with higher major complications (Clavien-Dindo grades III or IV) after resection of primary hepatocellular carcinoma in patients with compensated advanced chronic liver disease and portal hypertension [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is associated with a series of negative prognostic elements such as a higher rate of infection, longer hospitalization, hepatic encephalopathy, poor quality of life, and increased healthcare cost. Furthermore, sarcopenia is also associated with poor survival in patients with hepatocellular carcinoma (HCC) [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. While in these kinds of patients, many data demonstrate the prognostic burden and significance of sarcopenia, there are only a few data on its pathogenic mechanism [ 72 ].…”
Section: Creatine and Livermentioning
confidence: 99%